The relationships among metacognition, epistemic cognition, and physics identity constructs - Ulu, Yaren. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
The purpose of this study was to examine the relationships between epistemic cognition, metacognition, recognition, physics self-efficacy, interest and gender for high school students. Also, how epistemic cognition, metacognition, recognition, physics self-efficacy, interest and gender predicted physics identity was observed. The study involved a sample of 1197 high school students. Likert-type scales were used to gather the data. The Physics Personal Epistemology Questionnaire (PPEQ) was used to measure epistemic cognition. Also, to check students’ metacognition, the Metacognitive Awareness Inventory (MAI) was used. The physics identity scale measured interest, self-efficacy, recognition and physics identity. The data was collected via convenience sampling. Descriptive statistics, correlation and multiple regression analyses were used to analyze the data. The study showed that there was a very high positive correlation between identity, recognition, self-efficacy and interest constructs. Identity, recognition, self-efficacy and interest were moderately positively correlated with epistemic cognition and metacognition. Also, there was a high positive correlation between metacognition and epistemic cognition. Interest, recognition and self-efficacy positively predicted physics identity, while the strongest predictor was recognition. Metacognition and epistemic cognition did not predict physics identity. Regarding gender differences, males had higher levels of physics identity, recognition, interest and self-efficacy than females. On the other hand, there was no gender difference observed in metacognition and epistemic cognition.
Keywords: Epistemic logic.; Gender identity in education.